Manajemen Pendidikan Karakter Berbasis Nilai Islam: Integrasi Fungsi Manajerial dalam Penguatan Budaya Sekolah - Fifit Fajar Fauziah; Purwanto (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study aims to analyze the management of student character education at SMP IT Nur Hasan Senting and to formulate a managerial model of character education based on Islamic values and the Pancasila Student Profile. The study uses a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and document studies. Data analysis is conducted descriptively analytically through stages of data reduction, data presentation, and drawing conclusions. The research results indicate that character education management is implemented through an integrative managerial model that includes: (1) character values planning based on Islamic vision and curriculum policies; (2) character implementation through the integration of learning, religious habituation, and school culture; and (3) continuous evaluation based on behavior observation, reflection, and managerial supervision. This model positions the principal as a moral leader, teachers as value role models, and the school environment as an integrated character ecosystem. The novelty of this research lies in the formulation of an integrated Islamic character education management model that is not only oriented towards habituating behavior but also on strengthening the functions of education management in a systematic and sustainable manner. These findings provide a conceptual contribution to the development of Islamic education management by emphasizing that effective character education requires synergy between transformational leadership, a religious school culture, and the integration of values into the curriculum. The conceptual implications of this study enrich Islamic education studies by offering a managerial approach that combines modern management principles with Islamic moral values in shaping students who are faithful, virtuous, and competitive.